2015
DOI: 10.1017/s0007114515001750
|View full text |Cite
|
Sign up to set email alerts
|

Butyrylated starch intake can prevent red meat-induced O6-methyl-2-deoxyguanosine adducts in human rectal tissue: a randomised clinical trial

Abstract: Epidemiological studies have identified increased colorectal cancer (CRC) risk with high red meat (HRM) intakes, whereas dietary fibre intake appears to be protective. In the present study, we examined whether a HRM diet increased rectal O6-methyl-2-deoxyguanosine (O6MeG) adduct levels in healthy human subjects, and whether butyrylated high-amylose maize starch (HAMSB) was protective. A group of twenty-three individuals consumed 300 g/d of cooked red meat without (HRM diet) or with 40 g/d of HAMSB (HRM+HAMSB d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(63 citation statements)
references
References 51 publications
(73 reference statements)
1
60
1
1
Order By: Relevance
“…Research has revealed that intake of high‐amylose maize starch could increase intestinal SCFAs and the abundance of Parabacteroides , whereas high‐fat or low‐fat diets might result in the reduction of the microbial abundance . Thus, the postoperative Parabacteroides in our research might be affected by dietary factors.…”
Section: Discussionmentioning
confidence: 73%
“…Research has revealed that intake of high‐amylose maize starch could increase intestinal SCFAs and the abundance of Parabacteroides , whereas high‐fat or low‐fat diets might result in the reduction of the microbial abundance . Thus, the postoperative Parabacteroides in our research might be affected by dietary factors.…”
Section: Discussionmentioning
confidence: 73%
“…Corroborating these data, a recent study has shown that high red meat intake is associated with increased levels of the O6-Methyl-2′-deoxyguanosine mutagenic adduct in rectal epithelial cells and that a concomitant intake of fiber-derived products, such as butyrylated high-amylose, prevented this red meat-induced adduct formation (Le Leu et al, 2015). Gastrointestinal diseases, such as inflammatory bowel disease (IBD), can also induce the production of NOCs and thus potentially increase the risk of cancer (de Kok et al, 2005).…”
Section: Existing Theories To Explain Increased Disease Risks Of Rmentioning
confidence: 94%
“…Instead, approaches to reduce the risks associated with this dietary habit are more reasonable. Such approaches that have been suggested to date that are designed to reduce the harmful effects of red meat include: A moderate increase in dietary intake of calcium, which could “trap” heme iron and potentially reduce endogenous fat peroxidation (Pierre et al, 2013; Allam et al, 2011; Santarelli et al, 2013) and a diet rich in fiber and/or fiber-derived products could reduce NOC-induced adducts in colonic cells (Le Leu et al, 2015). Although both approaches showed promising effects in reducing colorectal cancer incidence, little is known about the role of these dietary interventions for the other types of cancer or for other diseases associated with red meat intake.…”
Section: Potential Approaches To Addressing the Human-specific Redmentioning
confidence: 99%
“…The gut microbiota is an essential component in the colonic microenvironment and an altered gut microbial composition or dysbiosis plays a critical role in the pathogenesis of intestinal as well as extra-intestinal diseases 31 . Butyrate acts as an energy source to epithelial cells 7 and inhibits genetic mutation 8 and oncogenic microRNA expression 32 in rectal biopsies. In addition, the role of SCFAs in regulating colonic regulatory T cells (cT Reg cells) in mice had been proposed 33, 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate is one of the three major forms of SCFAs and has both trophic and bioactive functions on host cells by correcting the altered ratio of the gut bacteria and protecting against the potential pro-inflammatory molecules 7 . It has been reported that increasing large-bowel butyrate supply has the potential to promote colonic integrity and lower the risk for colonic inflammation 8 . In that context this proof-of-concept study aimed to explore if RS4 (chemically modified RS), particularly through butyrate production, epigenetically regulates inflammatory gene expression in the gut.…”
Section: Introductionmentioning
confidence: 99%